Short-term in-season strength training with functional electromechanical devices versus pulley-based systems: performance and body-composition outcomes in handball players - Rodríguez Perea, Á.; Martínez-García, D.; Chirosa-Ríos, I. J.; Soto García, D. (International Journal of Sports Physiology and Performance, 2026)
Purpose: This study compared the effects of a 4-week in-season strength-training intervention using a functional electromechanical dynamometer (FEMD) versus a free-weight pulley-based (FWPB) system on throwing velocity, strength, and body composition in semiprofessional male handball players.